Effectiveness of School Feeding Programs on Student Participation and Academic Performance in Selected Schools of Sri Lanka - Dileepa Thathsara Olokku Patabendige; K.S.H.M.Vihare Walawwe Walter Senevirathne (Talenta Publisher, 2026)
Background: School nutrition programs are recognized for improving students’ health, yet their direct contribution to educational outcomes, particularly in remote and low-income junior secondary schools, remains insufficiently explored. Objective: This study investigates how school feeding programs influence student participation and academic performance. Methods: A mixed-methods explanatory design was used to compare schools with and without feeding programs. The sample consisted of 110 students, 25 teachers, and 20 parents from four socioeconomically diverse schools. Data were collected over three months through surveys, structured interviews, classroom observations, and analysis of attendance and academic records. Results: Findings indicated a 20% reduction in absenteeism and a 15% increase in average test scores in schools implementing nutrition programs. Students reported improved concentration and engagement, and teachers observed enhanced participation and fewer behavioural issues. Conclusions: School nutrition programs significantly support student learning and attendance. Integrating and expanding such initiatives, particularly in underserved areas, may further strengthen academic outcomes and overall student development.